2020
DOI: 10.1111/apt.15778
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: IBD‐associated colonic dysplasia prognosis in the videoendoscopic era (1990 to present)

Abstract: Background Introduction The prognosis of dysplasia in patients with IBD is largely determined from observational studies from the pre‐videoendoscopic era (pre‐1990s) that does not reflect recent advances in endoscopic imaging and resection. Aims To better understand the risk of synchronous colorectal cancer and metachronous advanced neoplasia (ie high‐grade dysplasia or cancer) associated with dysplasia diagnosed in the videoendoscopic era, and to stratify risk according to a lesion's morphology, endoscopic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…The development of advanced endoscopic resection techniques of non-polypoid dysplasia such as endoscopic submucosal dissection (ESD) and hybrid ESD/endoscopic mucosal resection (EMR), have allowed a greater number of these lesions to be endoscopically resected, when previously they would have been consigned to colectomy surgery 10 . More recent case series and smaller cohort studies from centres where high definition chromoendoscopy surveillance and advanced endoscopic resection techniques have been used have demonstrated lower rates of truly invisible dysplasia detection and lower AN progression rates after dysplasia has been endoscopically resected 810 . The univariate analyses in our study have indicated that whether or not a visible LGD lesion can be completely endoscopically resected is a more prominent risk factor than its morphology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of advanced endoscopic resection techniques of non-polypoid dysplasia such as endoscopic submucosal dissection (ESD) and hybrid ESD/endoscopic mucosal resection (EMR), have allowed a greater number of these lesions to be endoscopically resected, when previously they would have been consigned to colectomy surgery 10 . More recent case series and smaller cohort studies from centres where high definition chromoendoscopy surveillance and advanced endoscopic resection techniques have been used have demonstrated lower rates of truly invisible dysplasia detection and lower AN progression rates after dysplasia has been endoscopically resected 810 . The univariate analyses in our study have indicated that whether or not a visible LGD lesion can be completely endoscopically resected is a more prominent risk factor than its morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a high CRC risk, high-grade dysplasia (HGD) warrants preventive colectomy surgery or e n bloc endoscopic resection with intensive surveillance follow-up if unifocal 47 . The natural history of low-grade dysplasia (LGD) progression is less well defined with a wide range of rates reported for progression of LGD lesions to advanced neoplasia (HGD or CRC) due to the inclusion of historical data from small population studies with heterogenous terminology and limited follow-up 8 . The quality of endoscopic surveillance has also evolved over the past three decades with standardisation of surveillance technique, advances in imaging technology such as high definition white-light imaging and chromoendoscopy, and resection techniques such as endoscopic mucosal resection and submucosal dissection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] The natural history of low-grade dysplasia (LGD) progression is less well defined with a wide range of rates reported for progression of LGD lesions to advanced neoplasia (AN; HGD or CRC) due to the inclusion of historical data from small population studies with heterogeneous terminology and limited follow-up. 8 The quality of endoscopic surveillance has also evolved over the past three decades with standardisation of surveillance technique, advances in imaging technology such as high-definition white-light imaging…”
Section: Introductionmentioning
confidence: 99%